Menuju Birokrasi Berintegritas: Evaluasi Whistleblowing System (Studi pada Inspektorat Kota Malang) - Chazienul Ulum , Mochamad; Tiara Diva Raviona (Jurnal Ilmiah Administrasi Publik, 2023)
The OECD research highlights the effectiveness of whistleblowing systems in preventing corruption, prompting the Malang City Government to implement Mayor Regulation (Peraturan Walikota) No. 76 of 2015. Despite this effort, instances of corruption persisted. To assess the whistleblowing system at the Malang City Inspectorate, the research employed Robert E. Stake's Countenance Stake evaluation model, encompassing antecedents, transactions, and outcome indicators. Employing a descriptive qualitative approach, the study utilized semi-structured interviews, non-participant observation, and documentation studies for data collection. Findings reveal that, in terms of antecedents, the whistleblowing system aligns with guidelines, except for facilities and infrastructure. Transaction indicators mostly adhere to guidelines, with a suggested separation between handling Whistleblowing System (WBS) and public complaint (DuMas). Outcome indicators demonstrate a significant positive impact on the assessment of Integrity Zone-Bureaucratic Reform in several local government agencies of Malang City, underscoring the system's efficacy in fostering a corruption-free environment.